Improved outcome of myeloma related bone pain with oral analgesics and bisphosphonate therapy: A single-center experience from Pakistan. (1st December 2013) - Ali, Natasha; Moiz, Bushra; Silat, Hira; Rehan, Anam; Adil, Salman
<x xml:space="preserve">Abstract</x> Objective To determine the frequency of myeloma-related bone pain and to evaluate the effectiveness of various therapeutic options in such patients. Subjects and methods This was a retrospective review and we evaluated the patients with multiple myeloma over a period of 2 years from January 2005 to September 2012, for various types of bone pain and determined the optimum management for the same. Myeloma was diagnosed according to previously established criteria. All patients who presented with myeloma-related bone pain were included. Response to various analgesics was analyzed. Results During the study period n = 125 patients were diagnosed with multiple myeloma. Of these n = 89 (71%) presented with bone pain. There were 63 males and 62 females with median age of 58 years. Eighty patients complained of moderate pain, with backache as the commonest site which was observed in n = 30 patients (24%). Skeletal survey was diagnostic in 71%. Bone marrow involvement was seen in n = 55 patients with plasmacytosis ranging from 16 to 90%. Hypercalcemia was observed in 5% of the patients while IgG kappa was found in 22%. Fifty seven patients responded to World Health Organization step 1 and step 2 analgesic therapies alone while n = 32 patients required a combination of radiotherapy and surgery. Conclusion We observed that moderate bone pain is a frequent presenting symptom in multiple myeloma which in our experience responded very well to oral analgesics.